UZBEKISTAN YOUNG PEOPLE'S PERCEPTIONS OF FAMILY LIFE AND THE STATE OF SPIRITUAL AND PSYCHOLOGICAL READINESS FOR FAMILY (Universal International Scientific Journal, 2026)
This article highlights information about the future well-being of young people, as well as providing them with lessons from family life.
Keywords: economic, social, political, ecological, human development, happiness, education, upbringing.